The fast and the furriest - Behrens, Andy. (New York : Yearling, 2011)
The overweight and unathletic son of a famous former football star discovers that his equally fat and lazy dog is unexpectedly interested in competing in dog agility contests.
Originally published: New York : Alfred A. Knopf, 2010.
Sequoyah Nominee 2013
Keywords: Dogs -- Training -- Fiction; Competition (Psychology) -- Fiction; Football -- Fiction; Humorous fiction